Comparative Transcriptome Analysis of Male Sterile Anthers Induced by High Temperature in Wheat (Triticum aestivum L.) - Liu, Hongzhan; Sun, Zhongke; Hu, Lizong; Li, Chaoqiong; Wang, Xueqin; Yue, Zonghao; Han, Yulin; Yang, Guangyu; Ma, Keshi; Yin, Guihong (Frontiers in Plant Science, 2021)
Global warming will have a negative effect on agricultural production as high temperature (HT) stress can seriously threaten plant growth and reproduction. Male sterility caused by HT may be exploited by the creation of a male-sterile line, which has great potential for application in crop heterosis. Therefore, it is important to understand the molecular mechanisms of anther abortion induced by HT in wheat, which remain unclear at present. In this study, we performed phenotype changes and comparative transcriptome analysis of the male sterile anthers induced by HT in wheat. Compared with Normal anthers, cytological analysis indicated that HT-induced male sterile anthers were smaller and had no starch accumulation in pollen grains, which is consistent with the results observed by SEM. The 9601 differentially expressed genes (DEGs) identified by transcriptome sequencing compared with the Normal anthers were noticeably involved in the items, starch and sucrose metabolism, phosphatidylinositol signaling system, peroxidase activity and response to oxidative stress, and heme binding. In addition, TUNEL assays were performed and the results further confirmed the excessive accumulation of ROS in sterile anthers. Moreover, a total of 38 hub genes were obtained from the protein-protein interaction network analysis of these items, which involved HSP90, thioredoxin-like protein 1, POD, calreticulin, UGPase, sucrose synthase, PIP5K, cytochrome c, CBSX6-like, and so on. These findings provide insights for predicting the functions of the candidate genes, and the comprehensive analysis of our results is helpful for studying the abortive interaction mechanism induced by HT in wheat.